Pupil size variation as a response to stress in European catfish and its application for social stress detection in albino conspecifics - Slavík, Ondřej; Horký, Pavel; Velíšek, Josef; Valchářová, Tereza (PloS one, 2020)
Hormonal changes such as increased cortisol level in blood plasma in response to stress and social environmental stimuli are common among vertebrates including humans and typically accompanied by other physiological processes, such as changes in body pigmentation and/or pupil dilatation. The role of pupil size variation (PSV) as a response to stress have yet to be investigated in fish. We exposed albino and pigmented European catfish to short-term stress and measured changes in pupil size and cortisol level. Albinos showed lower pupil dilatation and higher cortisol levels than did pigmented conspecifics. A clear positive relationship between pupil dilatation and cortisol concentrations was observed for both pigmented and albino specimens, suggesting that PSV can be used as a stress indicator in fish, irrespective of albino's inability to express social communication by coloring. During the follow-up, we investigated whether a penultimate contest between albino individuals would impact contestants' social stress during subsequent contact. We observed PSV during the contact of unfamiliar albino catfish with different penultimate experiences (winner (W) and/or loser (L)). Then, the following treatment combinations were tested: WW, WL and LL. Twenty-four-hour contact of two unfamiliar catfish resulted in higher pupil dilatation among individuals with previous winner experience. Among treatment combinations, a WL contest displayed the highest pupil dilatation for winners. PSV reflected socially induced stress in individuals that was accompanied by the "winner" experience and dominancy in albinos. To conclude, the present study validates pupil dilatation as a non-invasive method to evaluate stress level in pigmented as well as albino fish in various contexts.
Keywords: komunikace zvířat; Catfishes; psychický stres; Hydrocortisone; Pupil; pupila; Animal Communication; Skin Pigmentation; pigmentace kůže; Animals; sumci; hydrokortison; Stress, Psychological; zvířata